Common Presenting Health Problems of Adult in Slum Dwellers of Chattogram City - Akter, Nahida; Jalal Uddin, M; Rownak, Nihad; Hossain, Nadia (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: The rapid growth of urbanization in Bangladesh has created some adverse effects on the overall urban environmental health of the cities. Among all, mass poverty, expansion of poor neighborhood, inadequate supply of urban services such as water, sanitation, waste disposal etc. are mostly responsible for health risks of urban people particularly in low socio-economic condition. A host of environmental and social problems beset the port city of Chattogram due to overcrowding of slums, which is largely blamed on unplanned urbanization. More than four hundred slums accommodating about 1 million of people are scattered across the city. Majority of these slums are situated on the Ice Factory road, along the railway tracks under Dewanhat Bridge, Sholosohor, Pahartali, Chittagong Railway Station, and Lalkhan Bazar MotiJhornaarea. The purpose of the study was to assess the pattern of common health problems of the adult members of the slum dwellers of Chattogram city. Materials and methods: A descriptive type of cross-sectional study was conducted from September to October 2022, using a sample of 321 respondents living in urban slums. Data was collected by face to face interview using a pretested mixed type of questionnaire. After collection, data was analyzed and resultswere presented as tables and figures. Results: Out of a total of 1492 family members of 321 families, there were 744 male and 748 female individuals. The most common presenting health problems among the adult respondents were Back pain and Generalized body-ache (24%), followed by Hypertension (16%), Headache (14%), Generalized Weakness (10%), Diabetes (8%), Asthma (8%), Cough (6%), Fever (5%), Chest Pain (4%), Anaemia (4%). Conclusion: The study concludes that physical structure of the neighborhood, and the physical and mental sufferings of its inhabitants are interdependent. To reduce the sufferings of inhabitants, their health hazards can be reduced with the combined efforts of the Government and the NGOs and the local people as well. Most of the slum dwellers are dependent on the pharmacy for their health problems. They are reluctant to take government health care facilities. Measures should be taken to make these facilities easily available to them. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 3-5